1974
DOI: 10.1021/ja00816a016
|View full text |Cite
|
Sign up to set email alerts
|

Ternary complexes in solution. XVIII. Stability enhancement of nucleotide-containing charge-transfer adducts through the formation of a metal ion bridge

Abstract: metal ion-nucleotide interactions are studied rather intensively,5 6 but still the detailed roles of metal ions are not widely known.Furthermore, up to now mainly simple binary metal ion-nucleotide complexes have been studied,5 6 but the reactions proceed within higher order species, like enzyme-metal ion-substrate complexes; hence, we believe that many of the unanswered questions may be approached by studying simple ternary complexes.7•8(5) A. T. Tu and M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 5 publications
(5 reference statements)
6
43
0
Order By: Relevance
“…This distance agrees favorably with the corresponding ones of Cu(Bipy)(ATP)2-(0.43 nm) and Cu(Bipy)-(ITP)Z-(0.5 nm), and for these ternary complexes it has been shown that an intramolecular charge-transfer adduct is formed between the aromatic parts of the two ligands, i.e. the purine moieties and 2,2'-bipyridyl [8,26]. In fact, the formation of such a metal ionbridged charge-transfer complex between 2,2'-bipyridyl and the guanosine moiety of GTP could be confirmed by the detection of an additional absorption in the ultraviolet region of the spectrum.…”
Section: E a Y~-a Y O supporting
confidence: 83%
“…This distance agrees favorably with the corresponding ones of Cu(Bipy)(ATP)2-(0.43 nm) and Cu(Bipy)-(ITP)Z-(0.5 nm), and for these ternary complexes it has been shown that an intramolecular charge-transfer adduct is formed between the aromatic parts of the two ligands, i.e. the purine moieties and 2,2'-bipyridyl [8,26]. In fact, the formation of such a metal ionbridged charge-transfer complex between 2,2'-bipyridyl and the guanosine moiety of GTP could be confirmed by the detection of an additional absorption in the ultraviolet region of the spectrum.…”
Section: E a Y~-a Y O supporting
confidence: 83%
“…In the present context it may also be pointed out that the existence of intramolecular stacks in Cu(Bpy)(S'AMP) complexes had been discovered about 15 years ago [17] in ultraviolet spectrophotometric measurements by the observation of a charge-transfer band due to the purine-pyridyl interaction; a tentative and simplified structure of this species is shown in Fig. 2.…”
Section: Note This Is Part 52 Of the Series Ternary Complexes In Solmentioning
confidence: 54%
“…About 40 years ago intramolecular aromatic-ring stacking was described for the first time [217,218] between heteroaromatic N bases (Arm), i.e., 2,2'-bipyridine or 1,10-phenanthroline, and AMP 2-, ADP 3-or ATP 4-, both ligands being bridged by a metal ion [200,[219][220][221].…”
Section: Of Stacksmentioning
confidence: 99%
“…Originally the interactions had been proven by UV spectrophotometry [217][218][219][220] and 1 H NMR shift measurements [201,222,223]. Later, complexes of the type M(Arm)(adenine nucleotide)…”
Section: Of Stacksmentioning
confidence: 99%